Green synthesis of silver nanoparticles using Salvadora persica L. and its antibacterial activity - Miri, A; Dorani, N; Darroudi, M; Sarani, M (Cellular and Molecular Biology, 2016)
The silver nanoparticles (AgNPs) shows special physicochemical properties, therefore they use many applications such as catalysis, health, electronic and optical. In this study, AgNPs was synthesized using aqueous extract of Salvadora persica bark. The synthesized AgNPs were characterized by UV-Vis spectroscopy, Powder X-ray diffraction (PXRD) and Transmission electron microscopy (TEM) methods. The optimal synthesis condition to prepare nanoparticles was determined as silver nitrate 3 mM, 5 ml of aqueous extract in the room temperature for 1 h. The TEM image of AgNPs showed the formation of spherical, non-uniform nanoparticles of mean size of 50 nm. The antibacterial activity of synthesized AgNPs was evaluated using disk diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods on Escherichia coli and Staphylococcus aureus bacteria. The MIC values of AgNPs were 100 and 400 µg/mL on E. coli and S. aureus, respectively. Also the MBC of AgNPs was 200 µg/mL for E. coli and there was no result observed for S. aureus bacteria. The results showed that synthesized nanoparticles have favorable antibacterial properties.